Adrenergic Repression of the Epigenetic Reader MeCP2 Facilitates Cardiac Adaptation in Chronic Heart Failure. Issue 7 (11th September 2015) - Mayer, Sandra C.; Gilsbach, Ralf; Preissl, Sebastian; Monroy Ordonez, Elsa Beatriz; Schnick, Tilman; Beetz, Nadine; Lother, Achim; Rommel, Carolin; Ihle, Hannah; Bugger, Heiko; Rühle, Frank; Schrepper, Andrea; et al.
<x xml:space="preserve">Abstract</x> Rationale: In chronic heart failure, increased adrenergic activation contributes to structural remodeling and altered gene expression. Although adrenergic signaling alters histone modifications, it is unknown, whether it also affects other epigenetic processes, including DNA methylation and its recognition. Objective: The aim of this study was to identify the mechanism of regulation of the methyl-CpG–binding protein 2 (MeCP2) and its functional significance during cardiac pressure overload and unloading. Methods and Results: MeCP2 was identified as a reversibly repressed gene in mouse hearts after transverse aortic constriction and was normalized after removal of the constriction. Similarly, MeCP2 repression in human failing hearts resolved after unloading by a left ventricular assist device. The cluster miR-212/132 was upregulated after transverse aortic constriction or on activation of α1- and β1-adrenoceptors and miR-212/132 led to repression of MeCP2. Prevention of MeCP2 repression by a cardiomyocyte-specific, doxycycline-regulatable transgenic mouse model aggravated cardiac hypertrophy, fibrosis, and contractile dysfunction after transverse aortic constriction. Ablation of MeCP2 in cardiomyocytes facilitated recovery of failing hearts after reversible transverse aortic constriction. Genome-wide expression analysis, chromatin immunoprecipitation experiments, and DNA methylation analysis identified mitochondrial genes and their transcriptional regulators as MeCP2 target genes. Coincident with its repression, MeCP2 was removed from its target genes, whereas DNA methylation of MeCP2 target genes remained stable during pressure overload. Conclusions: These data connect adrenergic activation with a microRNA—MeCP2 epigenetic pathway that is important for cardiac adaptation during the development and recovery from heart failure.